2013
DOI: 10.1371/journal.pone.0081900
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of αA-crystallin in High Myopia-Induced Dark Nuclear Cataract

Abstract: PurposeTo assess the etiology of early-onset dark nucleus in high-myopic patients and its relationship with the epigenetic regulation of αA-crystallin (CRYAA).MethodsWe reviewed clinical data from patients who underwent cataract surgery at our center in 2012. Lens epithelial samples were collected during capsulorhexis, whereas young lens epithelium was donated. Cataract type and severity were graded according to the Lens Opacity Classification System III (LOCS III). DNA methylation was analyzed by pyrosequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 30 publications
2
43
0
Order By: Relevance
“…Down-regulation of CRYAA via H19/miR-675 targeting reduces the expression of chaperones, which is able to bind to the denatured proteins induced by oxidative stress and thus preserve the transparency of the lens [57]. This may accelerate the oxidative modification of proteins in the nucleus, resulting in the pathogenesis of nuclear ARC [5,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Down-regulation of CRYAA via H19/miR-675 targeting reduces the expression of chaperones, which is able to bind to the denatured proteins induced by oxidative stress and thus preserve the transparency of the lens [57]. This may accelerate the oxidative modification of proteins in the nucleus, resulting in the pathogenesis of nuclear ARC [5,12].…”
Section: Discussionmentioning
confidence: 99%
“…Critical enzymes involved in DNA methylation, such as DNMT1 and MeCP2, have been identified in human lens epithelial cells (HLECs) [10,11]. Epigenetic regulatory processes, including DNA methylation of CRYAA [9,10,[12][13][14], histone acetylation of SOD1 [15] and long non-coding RNA (lncRNA)-MIAT and KCNQ1OT1 [16,17], have been implicated in the pathological cataractogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, with KR-1W analyzer, we measured the internal HOAs in pseudophakic highmyopic eyes with posterior staphyloma under different pupil sizes and found that posterior staphyloma might be the structure that offset the increased internal HOAs induced by mydriasis. On the basis of previous researches, 3,17,18 HM is of high prevalence in Asia, especially in China, and it affects people's visual function by large population both among children and adults. Relationship between HOAs and myopia is still under investigation.…”
Section: Figurementioning
confidence: 99%
“…Our previous study found that the promoter of the CRYAA gene, encoding a major structure protein, αA- crystallin, in the lens, is hypermethylated and hence downregulated in the lens of HMC patients, which could be one of the mechanisms that explains the higher severity of cataracts in highly myopic eyes [3], [9]. In addition to being a structural crystallin, αA- crystallin is also a molecular chaperone with a known function in preventing oxidative damages.…”
Section: Introductionmentioning
confidence: 99%